ANALISIS PENGGUNAAN BAHAN AJAR DALAM PEMBELAJARAN FISIKA DI SMAN 1 SOLOK SELATAN - Fitri Anabel, Haura (Universitas Negeri Malang, 2024)
The purpose of this study is to analyze the use of teaching materials by distributing questionnaires to teachers, students and the value of learning outcomes from students. This research employs a quantitative method for the study. sample being students of class XI Phase F Physics Specialization SMAN 1 Solok Selatan. The results of this study indicate the need for more appropriate and effective teaching materials to support students' abilities in the learning process, The results of questionnaires from teachers and students as well as student learning outcomes showed a low category. Thus, This indicates that the use of appropriate and effective teaching materials is needed to support students' abilities during the learning process.